Given `x^(2/3)+y^(2/3)=1`

Taking the first derivative implicitly we get:

`2/3x^(-1/3)+2/3y^(-1/3)(dy)/(dx)=0`

So

`2/3 y^(-1/3)(dy)/(dx)=-2/3x^(-1/3)`

------------------

`(dy)/(dx)=-x^(-1/3)y^(1/3)`

------------------

Then

`(d^2y)/(dx^2)=-[x^(-1/3)(1/3)y^(-2/3)(dy)/(dx)-1/3x^(-4/3)y^(1/3)]` substituting for `(dy)/(dx)`

`=-[x^(-1/3)(1/3)y^(-2/3)(-x^(-1/3)y^(1/3))-1/3x^(-4/3)y^(1/3)]`

`=-[-1/3x^(-2/3)y^(-1/3)-1/3x^(-4/3)y^(1/3)]`

`=1/3x^(-4/3)y^(-1/3)[x^(2/3)+y^(2/3)]` But `x^(2/3)+y^(2/3)=1` so

-------------------------

`(d^2y)/(dx^2)=1/3x^(-4/3)y^(-1/3)`

-------------------------

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now